Image and signal processing : 7th International Conference, ICISP 2016, Trois-Rivières, QC, Canada, May 30-June 2, 2016, Proceedings /: 7th International Conference, ICISP 2016, Trois-Rivières, QC, Canada, May 30-June 2, 2016, Proceedings. (2016) - Unknown
No abstract available